The Effects of Gender Discrimination, Workplace Harassment, and Workload on Job Satisfaction: The Mediating Role of Psychological Safety - Alina Raza; Laraib Khan; Arooj Fatima , (International Journal of Multidisciplinary Conference Proceedings (IJMCP), 2025)
Workplace well-being is crucial for organizational success, yet gender discrimination, workplace harassment, and excessive workload continue to pose significant threats to job satisfaction and employee morale. This study investigates the complex interplay between these workplace stressors and job satisfaction, with a particular focus on the mediating role of psychological safety. Grounded in Organizational Behavior Theory and the Psychological Safety Framework, the research aims to uncover the structural and psychological barriers that undermine job satisfaction in gender-diverse workplaces. A quantitative research design was employed, with data collected through a structured survey from 450 employees across various industries in Pakistan. Structural Equation Modeling (SEM) was utilized to analyze relationships among key variables and to test the mediating effect of psychological safety. The findings reveal that gender discrimination and workplace harassment significantly reduce job satisfaction, creating a toxic work environment that fosters stress, disengagement, and emotional exhaustion. Moreover, excessive workload further exacerbates dissatisfaction, leading to heightened burnout and decreased productivity